2020
DOI: 10.1590/1414-431x20209794
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates TGF-β1-induced EMT in intrauterine adhesion by activating Wnt/β-catenin signaling pathway

Abstract: Although estrogen has crucial functions for endometrium growth, the specific dose and underlying molecular mechanism in intrauterine adhesion (IUA) remain unclear. In this study, we aimed to investigate the effects of estrogen on epithelial-mesenchymal transition (EMT) in normal and fibrotic endometrium, and the role of estrogen and Wnt/β-catenin signaling in the formation of endometrial fibrosis. CCK-8 and immunofluorescence assay were performed to access the proliferation of different concentrations of estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…It is known that oestrogen participates in regulating EMT process. Oestrogen efficiently suppressed the EMT, contributing to reducing the area of fibrosis (Cao et al 2020). In GMECs, the inhibitory effect on EMT by oestrogen was revealed (Figure 2).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is known that oestrogen participates in regulating EMT process. Oestrogen efficiently suppressed the EMT, contributing to reducing the area of fibrosis (Cao et al 2020). In GMECs, the inhibitory effect on EMT by oestrogen was revealed (Figure 2).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, oestrogen (E2) is found to participate in the regulation of EMT progression. Oestrogen efficiently increased the number of endometrial glands and reduced the area of fibrosis as determined by the reduction in EMT in intrauterine adhesion animal models (Cao et al 2020). G protein-coupled estrogen receptor 1 (GPER1), a membrane estrogen receptor, is discovered to involve in the regulation of cell proliferation, migration and invasion (Molina et al 2017;Prossnitz & Barton, 2011).…”
mentioning
confidence: 99%
“…Furthermore, numerous studies have indicated that transforming growth factor (TGF)-β is a cytokine that participates in regulating diverse biological functions, including cell proliferation, apoptosis, and differentiation [ 11 , 12 ]. Importantly, previous studies have reported that TGF-β can induce endometrial fibrosis [ 13 , 14 ] and TGF-β treated ESC can serve as the in vitro model of IUA [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, subsequent IUA management is considered necessary when IUA occurs. Thus far, there have been many publications addressing the topic of the management of IUA [ 23 , 24 , 26 , 27 , 28 , 29 , 30 , 35 , 40 , 43 , 57 , 58 , 59 , 62 , 64 , 131 , 132 , 133 , 134 , 135 , 136 , 138 , 139 , 140 , 141 , 142 , 155 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Future Vision Of Iua Managementmentioning
confidence: 99%